Budi Pekerti Luhur Corporate Ethics: An Indigenous Indonesian Framework for Building Sustainable Corporate - Seno Hadi Saputro; Selamet Riyadi; Amri Amri (Widya Cipta: Jurnal Sekretari dan Manajemen, 2026)
This study develops and empirically validates the Budi Pekerti Luhur Corporate Ethics (BPLCE) framework as an indigenous Indonesian ethical model for building sustainable corporate culture in Bangka Belitung Province. Drawing from traditional Javanese moral philosophy, BPLCE comprises five dimensions: Integrity, Responsibility, Justice, Care, and Wisdom. Using structural equation modeling with survey data from 650 employees across multiple industries, we examine how BPLCE influences sustainable corporate culture directly and through three mediating mechanisms: organizational ethical climate, ethical leadership, and employee moral development. Results demonstrate that BPLCE significantly predicts sustainable corporate culture (β = 0.426, p < 0.001), explaining 69.7% of variance (R² = 0.697). The total indirect effect (β = 0.563) exceeds the direct effect, indicating substantial partial mediation (VAF = 56.9%). Organizational ethical climate shows the strongest mediation (β = 0.207), followed by ethical leadership (β = 0.194) and employee moral development (β = 0.162). Contextual factors significantly moderate these relationships. Industry sector exerts the strongest moderating effect (Δχ² = 18.742, p = 0.001), with mining demonstrating the highest impact (β = 0.512). Organizational size also moderates significantly (Δχ² = 7.926, p = 0.019), as larger organizations show stronger effects (β = 0.465). Regulatory environment positively moderates the relationship (β = 0.142, p = 0.002). Comparative analysis reveals BPLCE's superior explanatory power over Western virtue ethics (ΔR² = 0.083) and conventional CSR models (ΔR² = 0.099), confirming its cultural resonance and practical effectiveness for addressing sustainability challenges in emerging economies.